EFEKTIVITAS PERGANTIAN KEPEMIMPINAN DALAM RANGKA PENINGKATAN PELAYANAN PUBLIK PADA BADAN PENDAPATAN DAERAH PROVINSI JAWA TIMUR - Rita Kartika (DIA: Jurnal Administrasi Publik, 2018)
This study aims to determine and analyze the effectiveness of leadership change in order to improve public services at the Regional Income Board of East Java Province is expected to increase the potential of East Java's Original Income. The research method used guidance with interview and observation. Analytical technique using qualitative analysis based on phenomenon with descriptive format.The results based on the results of qualitative data processing through interviews and observations in general that this leadership change is considered very effective because it can encourage leaders to be encouraged to create new ideas that are innovative, brilliant, strategic so as to improve the quality and performance of public services both intensification and related extensification directly with the increase in the PAD. The effectiveness of the change of leadership of KUPTB has been considered successful because the changes are felt especially in the increase of local revenues in each KUPTB which is then calculated globally throughout East Java.